India under the British Colonial Rule and the Impact of the Indian Political Parties after Independence from 1900 to 2014 - Chamekh, Larbi (My University, 2018)
This book examines British rule in India or India during and after British colonial rule. Divided into three chapters. The first chapter deals with the historical context of India and the way in which the British colonization could be established in the subcontinent through trade. In addition, it shows the first Steps and strategies of the British on how they managed to colonize India. The second chapter explains Indian nationalism that had a big impact not only on Indian society but also on all in the world. The history of British Indian freedom has been dominated by the famous figure Gandhian political strategies that were particularly relevant to this movement that was they functioned widely and were characterized by democratic policies and essentially by civil liberation. Also, in this sense, this chapter highlights how Gandhi led the struggle for the freedom of the Indian British through passive and nonviolent resistance, and how these strategies have witnessed many positive changes in Indian society. India gained independence on August 15, 1947. However; he It was only the first break in colonial political control. The third examines the most important Indian political parties and their struggles for building a new nation after independence from India the rise of different factors in many aspects such as the political, economic and social aspects of the famous Indian scientist Nehru who gave the best to the Indian people to stay free and independent country.
Keywords: India; British colonization; Struggle for independence; Gandhi; Indian policy and rule